2001
DOI: 10.1159/000047730
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Seizures following Subcortical Infarcts

Abstract: Stroke is one of the most frequent causes of seizures in adulthood. Subcortical infarcts have been associated with post-stroke epileptic seizures, although less frequently than cortical ischaemia. We studied 113 patients from a hospital stroke registry. The patients had subcortical non-lacunar infarcts (64 striatocapsular infarcts, 13 thalamic, 8 choroidal artery territory, 28 internal border zone and white matter medullary infarcts) and at least 1 year of follow-up. Only 4 patients (3.5%) with striatocapsular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
4
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 16 publications
1
21
4
1
Order By: Relevance
“…Moreover, this study pointed that occipital localization of the DWI changes is also associated with LLW. The significance of the predominant location of the changes in the occipital cortical region remains unexplained, and contradicts with the previous reports which show these lesions primarily in the thalamus and the temporal lobe [22,26,28,29,30,31]. In general, a possible explanation for the pattern of hemispheric diffusion changes is the shift of water associated with protracted epileptical activity.…”
Section: Discussioncontrasting
confidence: 64%
“…Moreover, this study pointed that occipital localization of the DWI changes is also associated with LLW. The significance of the predominant location of the changes in the occipital cortical region remains unexplained, and contradicts with the previous reports which show these lesions primarily in the thalamus and the temporal lobe [22,26,28,29,30,31]. In general, a possible explanation for the pattern of hemispheric diffusion changes is the shift of water associated with protracted epileptical activity.…”
Section: Discussioncontrasting
confidence: 64%
“…68 For example, 1 retrospective study reported seizures in 3.5% of patients with lacunar stroke. 69 In SASS, seizures were reported in 8 (2.6%) of 307 patients with a diagnosis of lacunar infarction. 30 However, CT scanning was normal in the majority of these patients, and brain MRI was not performed; therefore, the possibility of cortical involvement cannot be completely excluded.…”
Section: Stroke Locationmentioning
confidence: 99%
“…Epilepsy can also be a consequence of subcortical infarcts [5] . The frequency of epilepsy in large series of CADASIL patients is approximately 10%, mostly occurring as a late symptom [1,2,6,7] .…”
Section: Discussionmentioning
confidence: 99%